Community-Based Approaches to Tackling Insecurity in Nigeria: Lessons and the Way Forward - Daniel Mevayerore Igbini; Anthony C. Nwokolobia (CV. Tripe Konsultan, 2026)
This study examined community-based approaches to tackling insecurity in Nigeria within the country’s prevailing socio-economic, political, and institutional contexts. It was prompted by the persistent escalation of insecurity, including kidnapping, banditry, insurgency, and communal conflicts, despite sustained efforts by state security agencies. The study is grounded in the Routine Activity Theory, which posits that crime occurs when a motivated offender, a suitable target, and the absence of a capable guardian converge in time and space. The study adopted the historical research design and relied on secondary sources of data, including textbooks, journal articles, government publications, policy documents, and credible online materials. Content analysis was employed to systematically examine and interpret the data through thematic categorization. Findings revealed that insecurity in Nigeria is driven by interrelated socio-economic and governance factors such as poverty, unemployment, weak institutional frameworks, corruption, and inadequate security capacity. It was also established that state-centered security strategies alone are insufficient, as they are constrained by limited manpower, weak intelligence systems, and declining public trust. The study further found that community-based security approaches, such as vigilante groups, neighborhood watch systems, and community policing, serve as important complementary mechanisms by enhancing surveillance, improving intelligence sharing, and strengthening rapid response to security threats. However, their effectiveness is limited by challenges such as weak regulation, inadequate training, and human rights concerns. The study concludes that a sustainable security framework in Nigeria requires an integrated approach that combines effective state institutions with well-structured and accountable community participation.